2013
DOI: 10.1093/mnras/stt2185
|View full text |Cite
|
Sign up to set email alerts
|

The mass–metallicity relation at z ∼ 1.4 revealed with Subaru/FMOS★

Abstract: We present a stellar mass-metallicity relation at z ∼ 1.4 with an unprecedentedly large sample of ∼ 340 star-forming galaxies obtained with FMOS on the Subaru Telescope. We observed K-band selected galaxies at 1.2 ≤ z ph ≤ 1.6 in the SXDS/UDS fields with M * ≥ 10 9.5 M ⊙ , and expected F(Hα) ≥ 5 × 10 −17 erg s −1 cm −2 . Among the observed ∼ 1200 targets, 343 objects show significant Hα emission lines. The gasphase metallicity is obtained from [N ii]λ6584/Hα line ratio, after excluding possible active galactic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
133
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(152 citation statements)
references
References 67 publications
16
133
3
Order By: Relevance
“…In the following, we summarize briefly the different observational data used here (for more details, the reader is referred to the corresponding papers): de los Reyes et al (2015) (medians and scatter at z ≈ 0.8), Hunt et al (2016) (medians with 75 per cent and 25 per cent quantile levels at 0.4 < z ≤ 0.7, 0.9 < z ≤ 1.8, 1.8 < z ≤ 2.8 and 2.8 < z ≤ 3.8), Ly et al (2016) (medians with the 16th and 84th percentiles at z = 0.5-1.0), Stott et al (2013) (median values and standard errors at z ≈ 0.84-1.47), Yabe et al (2014) (medians and bootstrap errors at z ≈ 1.4), Zahid et al (2014b) (fitted metallicities and observational uncertainties at z ≈ 1.6), Wuyts et al (2016) (mean values and standard errors at z ≈ 0.9 and z ≈ 2.3), Sanders et al (2015) (mean values and uncertainties at z ≈ 2.3), Cullen et al (2014) (fitted metallicities with uncertainties at z 2), Troncoso et al (2014) (individual measurements and their uncertainties at z ≈ 3.4) and Onodera et al (2016) (results from stacking analysis at z ≈ 3.3). Dotted lines in the large four panels indicate the fits to observations at different z given by Maiolino et al (2008).…”
Section: Evolution Of the M * -Z Sfgas Relationmentioning
confidence: 99%
“…In the following, we summarize briefly the different observational data used here (for more details, the reader is referred to the corresponding papers): de los Reyes et al (2015) (medians and scatter at z ≈ 0.8), Hunt et al (2016) (medians with 75 per cent and 25 per cent quantile levels at 0.4 < z ≤ 0.7, 0.9 < z ≤ 1.8, 1.8 < z ≤ 2.8 and 2.8 < z ≤ 3.8), Ly et al (2016) (medians with the 16th and 84th percentiles at z = 0.5-1.0), Stott et al (2013) (median values and standard errors at z ≈ 0.84-1.47), Yabe et al (2014) (medians and bootstrap errors at z ≈ 1.4), Zahid et al (2014b) (fitted metallicities and observational uncertainties at z ≈ 1.6), Wuyts et al (2016) (mean values and standard errors at z ≈ 0.9 and z ≈ 2.3), Sanders et al (2015) (mean values and uncertainties at z ≈ 2.3), Cullen et al (2014) (fitted metallicities with uncertainties at z 2), Troncoso et al (2014) (individual measurements and their uncertainties at z ≈ 3.4) and Onodera et al (2016) (results from stacking analysis at z ≈ 3.3). Dotted lines in the large four panels indicate the fits to observations at different z given by Maiolino et al (2008).…”
Section: Evolution Of the M * -Z Sfgas Relationmentioning
confidence: 99%
“…By this threshold, the uncertainty of the reproduced flux is less than ∼10%. The details are described by Yabe et al (2012Yabe et al ( , 2014. In total, the number of the galaxy samples that we use in this work is 271.…”
Section: Nir Spectroscopic Sample At Z ∼ 14mentioning
confidence: 99%
“…Local SFGs make a tight relation in the BPT diagram, which is caused by the anticorrelation between the oxygen abundance, 12+log(O/H), and the ionization parameter, qion (Dopita & Evans 1986;Dopita et al 2000Dopita et al , 2006a. Recent studies have revealed that z ∼ 2 galaxies have [N II] λ6584/Hα (N2) values higher than those of the local SFGs for a given [O III] λ5007/Hβ (O3) on average (Shapley et al 2005;Erb et al 2006;Brinchmann et al 2008;Liu et al 2008;Kewley et al 2013b;Steidel et al 2014;Masters et al 2014;Yabe et al 2014;Hayashi et al 2015;Shapley et al 2015;Sanders et al 2016;Kashino et al 2017). The z = 2 galaxies observed in the Keck Baryonic Structure Survey (KBSS; Steidel et al 2014) show the average of ∼ 0.4 dex excesses in [N II] λ6584/Hα.…”
Section: Introductionmentioning
confidence: 99%